Optical water quality variables (Secchi depth and Forel-Ule color indexes) observed during RV MARIA S. MERIAN cruise MSM65 (2017-06-25 – 2017-07-19, GREENHAB II) - Rohan Henkel; Axel Braun; Veloisa J Mascarenhas; Daniela Pieck; Daniela Voß; Oliver Zielinski (PANGAEA, 2025)
Water clarity and color were observed during the cruise MSM65 (GREENHAB II, 2017-06-25 – 2017-07-19) with RV MARIA S MERIAN from St. John extquotesingles, Canada to Nuuk, Greenland using a white Secchi disc with a diameter of 40 cm and a Forel-Ule color scale. The Secchi depth (SD) was recorded as a relative measure of water clarity at each in situ station during day time. At half SD the apparent color of the water above the submerged Secchi disc was determined using the Forel-Ule color scale. A Forel-Ule color scale is a classic tools used to differentiate the percieved color of water based on a scale from 1 (indigo blue) to 21 (cola brown). The measurements were conducted as recommend in literature (Garaba and Zielinski, 2015; Wernand, 2011; Wernand and van der Woerd, 2010).